HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN SIKAP IBU HAMIL TENTANG SENAM HAMIL DI KLINIK JULIANA DALIMUNTHE KABUPATEN DELI SERDANG 2021 - ELVI SEPRIANI; LENI MARLINA TUMANGGOR (LP2MTBM MAKARIOZ, 2021)
Pregnant gymnastics is a movement exercise therapy given to pregnant women to prepare themselves, both physical andmental preparation to face and prepare for a fast, safe and spontaneous delivery. This study aims to identify the relationshipof knowledge with the attitude of pregnant women about pregnant gymnastics at the Juliana Dalimunthe Tembung clinic ofDeli Serdang Regency in 2021. The research design used in this study is descriptive of correlational with a cross sectionalapproach with a large sample of as many as 40 people with a total sampling method. The instruments in this study includedquestionnaires that included demographic data, knowledge questions and attitude revelations about pregnant gymnastics.The results showed that the majority of pregnant women were knowledgeable enough as many as 21 people (52.5%) andwere positive as many as 25 people (62.5%) towards pregnant gymnastics. After the chi-square test was concluded therewas a significant relationship between knowledge and the attitude of pregnant women about pregnant gymnastics becauseof the value of p value < 0.05 or (0.000>0.05). It is expected that health workers can do health promotion and socializationabout Pregnant Gymnastics so as to foster awareness of pregnant women to want to do pregnant gymnastics, especially inthe second trimester of pregnancy.